Urinary Tract Infection as a Risk Factor for Preterm Delivery: A Tertiary Hospital-Based Study - Pangastuti, Nuring; Indraswari, Lathifa N; Prawitasari, Shinta (Indonesian Socety of Obstetrics and Gynecology, 2019)
ABSTRACT   Background: Preterm delivery is the leading cause of perinatal morbidity and mortality in developing countries. Urinary tract infection is one of the infectious diseases that often occur in pregnant women. Despite, the correlation between bacteriuria, either symptomatic or asymptomatic, and preterm delivery is still controversial. Purpose: To investigate the correlation between the incidence of UTI and preterm delivery. Methods: We conducted a cohort retrospective research using patients medical records. We analyzed the incidence of UTI and preterm delivery from January to December 2015, in Dr. Sardjito Hospital, Yogyakarta. Results: The sample of this study covers medical records of 45 patients with preterm delivery. From total sampel, only 25 patients (55.6%) underwent urinalysis. Of these 25 patients, 15  (60%) had UTIs and all of them had preterm delivery. The result showed 13 (86.7%) of 15 patients with bacteriuria were asymptomatic. Bacteriuria that was found in 15 subjects was not statistically significant when compared to preterm delivery indicated with relative ratio of 1,083 (p = 0,581 > 0,05). Multivariate logistic regression analysis showed that preterm delivery were not directly related to UTI (p = 0.704), gestational age (p = 0.274), symptom of UTI (0.699), history of UTI (p=0.999), and history of coitus (p = 0.872). Conclusion: The study revealed that preterm delivery was not related to UTI. Other causes should be considered. However, the discovery of asymptomatic bacteriuria in patients with preterm delivery indicated that this might be one of the risk factors for preterm delivery. Routine urinalysis test for pregnant woman considered for the prevention.   Keywords: UTIs, preterm delivery, bacteriuria